A New Circumscribed Self-Excited Spherical Strange Attractor. (11th June 2021) - Ramamoorthy, Ramesh; Jamal, Sajjad Shaukat; Hussain, Iqtadar; Mehrabbeik, Mahtab; Jafari, Sajad; Rajagopal, Karthikeyan
Abstract : Studying new chaotic flows with specific characteristics has been an open-ended field of exploring nonlinear dynamics. Investigation of chaotic flows is an area of research that has been taken into consideration for many years; thus, it helps in a better understanding of the chaotic systems. In this paper, an original chaotic 3D system, which has not been investigated yet, is presented in spherical coordinates. A unique feature of the proposed system is that its velocity becomes zero for a specific value of the radius variable. Hence, the system's attractor is expected to be stuck on one side of a plane in spherical coordinates and inside or outside a sphere in the corresponding Cartesian coordinates. It means that the attractor cannot pass through the sphere or even touch it. The introduced system owns two unstable equilibria and a self-excited strange attractor. The 1D and 2D system's bifurcation diagrams concerning the alteration of two bifurcation parameters are plotted to investigate the system's dynamical properties. Moreover, the system's Lyapunov exponents in the corresponding period of bifurcation parameters are calculated. Then, two 2D basins of attraction for two different third dimension values are explored. Based on the basin of attraction, it can be found that the sphere has attraction itself, partially, and some initial conditions are led to the sphere, not to the strange attractor. Ultimately, the connecting curves of the proposed system are explored to find an informative 1D set in addition to the system's equilibria.